Analysis of Queue System On Passport Service Unit Class 1 Immigration Office of Makassar - Abdy, Muhammad; Sanusi, Wahidah; Mukarram, Trys (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2017)
Queuing is a common thing in everyday life and can be found in the manufacturing sector as well as in the service sector.No exception at the agency or government office.ULP (Passport Service Unit) The First Class Immigration Office of Makassar City is a technical implementing unit performing the functions of the Directorate General of Immigration in a certain region or city providing services in the field of immigration.This study aims to determine the queuing model applied to the Passport Service Unit of the First Class Immigration Office of Makassar City and find out whether the level of service provided is optimal.In the analysis process used manual calculation and supportby software POM for Windows 3.Based on analysis of data obtained after the study, modela queues applied to ULP (Unit Passport Service) Class I Immigration Office of Makassar is the (M/M/S):(FCFS/âˆž/âˆž).Queue system at Passport Service Unit First Class Immigration of the Office of Makassar City can be said to be normal on a typical day, because it has met the old standard of service time. So that the system applied is optimal.